Doped polycrystalline silicon material and preparation method thereof, battery and microwave annealing furnace

By applying heat and microwave treatment to a tunneling oxide layer and polysilicon or amorphous silicon layer with doping elements, the doping concentration is increased, enhancing the passivation and reducing resistance in TOPCON batteries.

CN119153582APending Publication Date: 2024-12-17JIANGSU MICROVIA NANO EQUIP TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411339269.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Existing methods for preparing doped polysilicon layers in TOPCON batteries, such as PECVD, result in low doping concentrations and inactive atoms, limiting performance and requiring improvements in passivation and contact resistance.

Method used

A method involving sequential formation of a tunneling oxide layer and a polysilicon or amorphous silicon layer with doping elements, followed by simultaneous heat and microwave treatment, increasing the doping concentration by an order of magnitude.

Benefits of technology

The method significantly enhances the passivation performance and reduces resistance in the doped polysilicon layer and metal contact, improving the battery's open circuit voltage, series resistance, and fill factor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides a preparation method of a doped polycrystalline silicon material, which comprises the following steps: sequentially forming a tunneling oxide layer and a polycrystalline silicon layer or an amorphous silicon layer containing doping elements on the surface of a base material, and carrying out microwave treatment while carrying out heat treatment on the obtained material to obtain the doped polycrystalline silicon material, the power of the microwave treatment is 50 W to 1000 W. The invention further provides a doped polycrystalline silicon material, a TOPCON battery, a preparation method of the TOPCON battery and a microwave annealing furnace. According to the invention, microwave treatment is carried out under specific power while heat treatment is carried out on the polycrystalline silicon layer or the amorphous silicon layer containing the doping elements, and the doping concentration can be improved by one order of magnitude, so that the passivation performance of the battery is greatly improved, and meanwhile, the resistance generated by contact between the doped POLY layer and metal is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of photovoltaic cells, and in particular to a doped polysilicon material and a preparation method thereof, a cell and a microwave annealing furnace. Background Art

[0002] At present, the existing technology often uses plasma enhanced chemical vapor deposition (PECVD) technology to prepare the doped polysilicon layer (POLY layer) required for TOPCON type batteries, including P-type doping and N-type doping. The preparation method generally uses a gaseous alkane chemical source as a reactant to achieve the growth and online doping of the POLY layer. The doping concentration of the prepared doped polysilicon is low, which limits its performance, and a large number of atoms are not activated.

[0003] The doping concentration of the existing high-temperature activation method has reached its upper limit. Technical issues such as how to further increase the activation concentration of doped atoms, improve the passivation performance of the battery, and reduce the contact resistance of the doped POLY layer and the metal contact layer need to be solved urgently. Summary of the invention

[0004] In view of this, the present application provides a method for preparing a doped polysilicon material. The method provided in the present application can increase the doping concentration of the polysilicon layer, thereby improving the passivation performance of the battery and reducing the resistance generated by the doped POLY layer and the metal contact.

[0005] At present, plasma enhanced chemical vapor deposition (PECVD) technology is generally used to prepare the doped polysilicon layer (POLY layer) required for TOPCON batteries, including P-type doping and N-type doping. Gaseous alkane chemical sources as reactants are the main means to achieve the growth of POLY layers and online doping. For example, when depositing N-type POLY layers, inert gases such as silane (SiH4), phosphine (PH3), hydrogen (H2) or argon (Ar) are generally used; when depositing P-type POLY layers, inert gases such as silane (SiH4), borane (B2H6) or trimethyl boron (TMB), hydrogen (H2) or argon (Ar) are generally used. Among them, SiH4 is the main element of the bulk layer of the growth POLY layer; inert gases such as H2 and Ar are used as gases to dilute or regulate the bonding structure of POLY. Group III or Group V alkane gases such as phosphine (PH3), borane (B2H6) or trimethyl boron (TMB) are used as dopants, generally mixed with hydrogen or argon, such as 2% PH3 and 98% H2, as source gases. After annealing, the doping elements P or B are activated to achieve the doping of the polysilicon layer. However, the doped polysilicon prepared by the above method, especially the N-type doped polysilicon layer, can only reach a doping concentration of 2~5×10 20 cm -3 The ECV (activation concentration) results are shown in the figure below. Figure 1As shown, its performance is limited, and there are still a large number of atoms that are not activated. The SIMS (unactivated concentration) test results are shown in the figure Figure 2 shown.

[0006] Based on this, the present application provides a method for preparing a doped polysilicon material, comprising: sequentially forming a tunneling oxide layer and a polysilicon layer or an amorphous silicon layer containing doping elements on the surface of a silicon substrate, and simultaneously performing a heat treatment and a microwave treatment on the obtained material to obtain a doped polysilicon material; the power of the microwave treatment is 50W to 1000W.

[0007] The present application performs microwave treatment at a specific power while heat treating the polysilicon layer or amorphous silicon layer containing doping elements, which can increase the doping concentration, especially the doping concentration of P, by an order of magnitude, thereby greatly improving the passivation performance of the battery and reducing the resistance generated by the doped POLY layer and the metal contact. In some specific implementations, the power of the microwave treatment is 50W to 1000W.

[0008] In some specific implementations, the time of the microwave treatment is 5 min to 60 min, and the frequency of the microwave treatment is 300 MHz to 300 GHz.

[0009] In some specific implementations, the power of the microwave treatment is 100 W to 800 W, the frequency of the microwave treatment is 800 MHz to 100 GHz, and the time of the microwave treatment is 10 min to 50 min.

[0010] In some specific implementations, the heat treatment temperature is 600° C. to 1200° C., the heat treatment is performed in an atmosphere of nitrogen or oxygen, and the heat treatment time is 20 min to 60 min.

[0011] In some specific implementations, the thickness of the tunnel oxide layer is 0.1 nm to 2.5 nm.

[0012] In some specific implementations, a polysilicon layer or an amorphous silicon layer containing doping elements is formed according to the following method:

[0013] forming a polysilicon layer or an amorphous silicon layer on the surface of the tunnel oxide layer;

[0014] forming a diffusion source on the surface of the polycrystalline silicon layer or the amorphous silicon layer, and forming a polycrystalline silicon layer or an amorphous silicon layer containing doping elements after heat treatment;

[0015] Alternatively, a polycrystalline silicon layer or an amorphous silicon layer containing doping elements is formed by the following method:

[0016] Silicon-containing gas, doping element-containing gas and carrier gas are vapor-deposited on the surface of the tunneling oxide layer to form a polysilicon layer or an amorphous silicon layer containing doping elements.

[0017] The present application also provides a doped polysilicon material, comprising a substrate, a tunneling oxide layer and a doped polysilicon layer stacked in sequence, wherein the doping concentration of the doped polysilicon layer is 0.8×10 21 cm -3 Up to 2×10 21 cm -3 .

[0018] The present application also provides a TOPCON cell, comprising the doped polysilicon material described in the above technical solution.

[0019] The present application provides a method for preparing a TOPCON battery, which comprises:

[0020] A textured surface and an emitter are sequentially formed on the first surface of the substrate, and a tunneling oxide layer and a polysilicon layer or an amorphous silicon layer containing doping elements are sequentially formed on the second surface, and the obtained material is subjected to a heat treatment and a microwave treatment at the same time to convert the polysilicon layer or the amorphous silicon layer containing doping elements into a doped polysilicon layer; the power of the microwave treatment is 50W to 1000W;

[0021] forming a passivation film and a first anti-reflection film on the emitter in sequence, and forming a second anti-reflection film on the surface of the doped polysilicon layer;

[0022] A first electrode and a second electrode are formed on the surfaces of the first anti-reflection film and the second anti-reflection film respectively.

[0023] The present application also provides a microwave annealing furnace, comprising a heating cavity, wherein a high-frequency coil for generating microwaves is disposed outside the heating cavity, and a quartz cavity is disposed inside the heating cavity, wherein a quartz boat for carrying samples is disposed inside the quartz cavity.

[0024] The present application sequentially forms a tunneling oxide layer and a polysilicon layer or an amorphous silicon layer containing doping elements on the surface of a substrate, and simultaneously performs microwave treatment on the obtained material to obtain a doped polysilicon material; the power of the microwave treatment is 50W to 1000W. The present application performs microwave treatment at a specific power while simultaneously performing heat treatment on the polysilicon layer or the amorphous silicon layer containing doping elements, which can increase the doping concentration by an order of magnitude, thereby greatly improving the passivation performance of the battery, while reducing the resistance generated by the doped POLY layer and the metal contact. Experimental results show that the method provided in the present application can increase the doping concentration, especially the doping concentration of P, to 0.8×10 21 cm -3 Up to 2×10 21 cm -3The open circuit voltage Uoc of the N-topcon battery made with it can be increased by 1~2mv, the series resistance Rs of the battery can be reduced by 0.1 milliohms~0.2 milliohms (mohm), and the fill factor FF can be increased by 0.1%~0.3%. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the test result of ECV (activation concentration) of the doped POLY layer after high temperature annealing and crystallization;

[0026] Figure 2 This is the SIMS (unactivated concentration) test result of the doped POLY layer after high-temperature annealing and crystallization;

[0027] Figure 3 A schematic diagram of the structure of a microwave annealing furnace provided in an embodiment of the present application;

[0028] Figure 4 A schematic diagram of the stacked structure of the doped polysilicon material provided in this application;

[0029] Figure 5 A schematic diagram of the stacked structure of the TOPCON battery provided in this application;

[0030] Figure 6 This is a graph showing the ECV (activation concentration) test results of the doping crystalline silicon material provided in Example 1 of the present application. DETAILED DESCRIPTION

[0031] It should be understood that the expression "one or more of..." includes each of the items recited after the expression individually and in various different combinations of two or more of the recited items, unless otherwise understood from the context and usage. The expression "and / or" in combination with three or more recited items should be understood to have the same meaning, unless otherwise understood from the context.

[0032] The use of the terms "comprising", "having" or "containing", including their grammatical synonyms, should generally be understood as open and non-restrictive, for example not excluding other unrecited elements or steps, unless otherwise specifically stated or otherwise understood from the context.

[0033] It should be understood that the order of steps or the order in which certain actions are performed is not important as long as the application is still operable. In addition, two or more steps or actions can be performed simultaneously.

[0034] The use of any and all examples or exemplary language, such as "for example" or "including", herein is intended only to better illustrate the present application and does not limit the scope of the present application unless the claims are set forth. No language in this specification should be construed as indicating that any non-claimed element is essential to the practice of the present application.

[0035] In addition, the numerical ranges and parameters used to define the present application are approximate values, and the relevant values ​​in the specific embodiments have been presented as accurately as possible. However, any numerical value inherently inevitably contains standard deviations due to individual test methods. Therefore, unless otherwise expressly stated, it should be understood that all ranges, quantities, values ​​and percentages used in this disclosure are modified by "about". Here, "about" generally refers to the actual value within plus or minus 10%, 5%, 1% or 0.5% of a specific value or range.

[0036] The present application provides a method for preparing a doped polysilicon material, comprising: sequentially forming a tunneling oxide layer and a polysilicon layer or an amorphous silicon layer containing doping elements on a substrate surface, and simultaneously performing a heat treatment and a microwave treatment on the obtained material to obtain a doped polysilicon material; the power of the microwave treatment is 50W to 1000W.

[0037] The present application first provides a substrate, then forms a tunneling oxide layer on the surface of the substrate, then forms a polysilicon layer or an amorphous silicon layer containing doping elements on the surface of the tunneling oxide layer, and finally performs heat treatment and microwave treatment on the obtained material to obtain a doped polysilicon material with a higher doping concentration.

[0038] The present application uses a substrate as a raw material, and the present application has no special restrictions on the substrate, which can be a silicon substrate, such as an n-type silicon wafer, etc. The present application first forms a tunneling oxide layer, i.e., a silicon dioxide layer, on one surface of the substrate. The present application has no special restrictions on the method for forming the tunneling oxide layer, including but not limited to one or more methods such as wet oxidation, ozone oxidation, thermal growth, plasma enhanced chemical vapor deposition (PECVD) or plasma enhanced atomic layer deposition (PEALD).

[0039] In some specific implementations, the wet oxidation is specifically to oxidize the silicon substrate using a mixed solution of H2O2 and HNO3 to form a tunneling oxide layer on the surface of the silicon substrate. In some specific implementations, in the mixed solution, the mass concentration of H2O2 is 1%~5%, preferably 2%~4%; the concentration of HNO3 is 0.01%~1%, preferably 0.1%~0.8%, the oxidation temperature is 40°C to 60°C, and the oxidation time is 10min to 20min. In a typical implementation, the silicon substrate can be immersed in the mixed solution to achieve oxidation.

[0040] In some specific implementations, the ozone oxidation to form the tunneling oxide layer is specifically: oxidizing the surface of the silicon substrate with ozone, for example, passing ozone into the surface of the silicon substrate. The present application has no special restrictions on the specific process parameters of the ozone oxidation, and those skilled in the art can select as needed.

[0041] In some specific implementations, the thermal growth is specifically: forming a tunneling oxide layer on the surface of the silicon substrate under heat treatment conditions. In some specific implementations, the heat treatment temperature is 550° C. to 650° C., the heat treatment time is 4 min to 10 min, and the heat treatment pressure is 0.09 MPa to 0.15 MPa.

[0042] In some specific implementations, the plasma enhanced chemical vapor deposition is specifically to form a tunnel oxide layer by chemical vapor deposition under plasma enhanced conditions. In some specific implementations, the gas for plasma enhanced chemical vapor deposition is N2O, the pressure thereof is 70Pa to 200Pa, and the flow rate thereof is 1000sccm to 1200sccm.

[0043] In some specific implementations, the plasma enhanced atomic layer deposition is specifically to form a tunneling oxide layer by atomic layer deposition under plasma enhanced conditions. The present application has no special restrictions on its specific process and parameters, and those skilled in the art can select them according to the required objectives.

[0044] In some specific implementations, the thickness of the tunnel oxide layer is 0.1 nm to 2.5 nm, preferably 0.5 nm to 1.8 nm, and more preferably 0.8 nm to 1.4 nm.

[0045] After the tunneling oxide layer is formed, a polycrystalline silicon layer or an amorphous silicon layer containing doped elements is formed on its surface. The present application has no special restrictions on the method of forming the polycrystalline silicon layer or the amorphous silicon layer containing doped elements, including but not limited to one or more methods such as low pressure chemical vapor deposition (LPCVD), plasma enhanced chemical vapor deposition (PECVD) or hot filament chemical vapor deposition (HWCVD).

[0046] In some specific implementations, the low pressure chemical vapor deposition is specifically:

[0047] forming a polysilicon layer or an amorphous silicon layer on the surface of the tunnel oxide layer by low pressure chemical vapor deposition;

[0048] A diffusion source is formed on the surface of the polycrystalline silicon layer or the amorphous silicon layer, and a polycrystalline silicon layer or an amorphous silicon layer containing doping elements is formed after heat treatment.

[0049] Specifically, the present application first places a silicon substrate formed with a tunneling oxide layer into a furnace tube of a vapor deposition furnace, introduces SiH4, performs low-pressure chemical vapor deposition, and forms a polycrystalline silicon layer or an amorphous silicon layer on the surface of the tunneling oxide layer. In some specific implementations, the volume flow rate of SiH4 is 1000sccm to 3000sccm, preferably 1500sccm to 2500sccm; the temperature of the low-pressure chemical vapor deposition is 550°C to 620°C, the pressure is 30Pa to 300Pa, and the time is 30min to 50min. It can be understood by those skilled in the art that polycrystalline silicon or amorphous silicon can be formed by controlling the reaction conditions, and the present application has no special restrictions on this.

[0050] After forming a polysilicon layer or an amorphous silicon layer, the present application forms a diffusion source on its surface, and after heat treatment, the diffusion source allows the doping elements in the diffusion source to enter the polysilicon layer or the amorphous silicon layer to form a doped polysilicon layer. In some specific implementations, the diffusion source is a phosphorus-containing compound or a boron-containing compound, which can be carried into the diffusion device by nitrogen or oxygen to form a diffusion source. In some specific implementations, the phosphorus-containing compound includes but is not limited to phosphorus oxychloride, phosphine (PH3), etc., preferably phosphorus oxychloride; the boron-containing compound can be borane (B2H6) or trimethylboron (TMB), preferably borane. In some specific implementations, the volume flow rate of the nitrogen or oxygen is 200sccm to 1000sccm, preferably 300sccm to 800sccm.

[0051] After the diffusion source is formed, it is heat treated to allow the doping elements therein to enter the polysilicon layer or the amorphous silicon layer, and at the same time, the amorphous silicon is converted into polysilicon to form a doped polysilicon layer. In some specific implementations, the heat treatment temperature is 860° C. to 920° C., and the time is 30 min to 45 min.

[0052] A typical operation step of low pressure chemical vapor deposition (LPCVD) is as follows:

[0053] Raise the temperature of the furnace tube of the chemical vapor deposition equipment to 550°C~620°C, evacuate the gas in the tube, introduce 1000scmm~3000scmm SiH4, control the pressure to 30Pa~300Pa, and deposit for 30min~50min to form an amorphous silicon layer or a polycrystalline silicon layer on the tunnel oxide layer;

[0054] The sample is then placed in a diffusion device, the furnace tube of the diffusion device is heated to 860°C~920°C, 200sccm~1000sccm of N2 carrying phosphorus oxychloride is introduced, and O2 is introduced at the same time to form a diffusion source on the surface of the amorphous silicon layer or polycrystalline silicon layer for 5min~10min, and then high-temperature treatment is performed for 30min~45min to diffuse the doping elements into the amorphous silicon layer or polycrystalline silicon layer to form a doped amorphous silicon / polycrystalline silicon layer.

[0055] In some specific implementations, the specific steps of the plasma enhanced chemical vapor deposition are: subjecting a silicon substrate formed with a tunneling oxide layer to plasma enhanced chemical vapor deposition under the conditions of introducing a silicon-containing gas, a dopant element-containing gas and a carrier gas, to form a polycrystalline silicon layer or an amorphous silicon layer material containing dopant elements on the surface of the tunneling oxide layer. In some specific implementations, the silicon-containing gas includes but is not limited to SiH4; the dopant element-containing gas includes but is not limited to phosphorus oxychloride, phosphine (PH3), borane (B2H6) or trimethyl boron (TMB), etc.; the carrier gas includes but is not limited to argon, H2, etc. In some specific implementations, the volume flow rate of silicon-containing gas, such as SiH4, is 2000sccm to 4000sccm, preferably 2500sccm to 3500sccm; the volume flow rate of dopant element-containing gas, such as PH3, is 500sccm to 3500sccm, preferably 1000sccm to 3000sccm; the volume flow rate of carrier gas, such as H2, is 6500sccm to 12000sccm, preferably 7000sccm to 11000sccm. In some specific implementations, the pressure of the plasma enhanced chemical vapor deposition is 200Pa to 600Pa, preferably 300Pa to 500Pa; the temperature is 350℃ to 500℃, preferably 400℃ to 450℃; the time is 10min to 15min. In some specific implementations, the power supply power of the plasma enhanced chemical vapor deposition equipment is 10000W to 18000W, the power supply ton / off=3:54, etc.

[0056] A typical operation process of plasma enhanced chemical vapor deposition (PECVD) is as follows:

[0057] The temperature of the furnace tube of plasma enhanced chemical vapor deposition is raised to 350°C~500°C, the furnace tube is evacuated, 2000sccm~4000sccm of SiH4, 500sccm~3500sccm of PH3, and 6500sccm~12000sccm of H2 are introduced, the pressure is controlled to be 200Pa~600Pa, the power is set to 10000W~18000W, the power ton / off=3:54, and the deposition is carried out for 10~15min to directly form a doped amorphous silicon layer or a polycrystalline silicon layer.

[0058] In some specific implementations, the specific steps of the hot wire chemical vapor deposition are: after the silicon-containing gas, the dopant element-containing gas and the carrier gas are decomposed, the hot wire chemical vapor deposition is performed on the surface of the silicon substrate with the tunneling oxide layer formed thereon, and a polycrystalline silicon layer or an amorphous silicon layer containing the dopant element is formed on the surface of the tunneling oxide layer. In some specific implementations, the silicon-containing gas includes but is not limited to SiH4; the dopant element-containing gas includes but is not limited to phosphorus oxychloride, phosphine (PH3), borane (B2H6) or trimethyl boron (TMB), etc.; the carrier gas includes but is not limited to argon, H2, etc. In some specific implementations, the volume flow rate of silicon-containing gas, such as SiH4, is 200 sccm to 1000 sccm, preferably 300 sccm to 800 sccm; the volume flow rate of dopant element-containing gas, such as PH3, is 100 sccm to 1000 sccm, preferably 200 sccm to 800 sccm; the volume flow rate of carrier gas, such as H2, is 1500 sccm to 3000 sccm, preferably 2000 sccm~2500 sccm. In some specific implementations, the decomposition temperature is 1600°C to 2000°C, preferably 1700°C to 1900°C. In some specific implementations, the pressure of the hot wire chemical vapor deposition is 20Pa to 150Pa, preferably 50Pa~100Pa; the time is 4min to 8min.

[0059] A typical process of hot wire chemical vapor deposition (HWCVD) is as follows:

[0060] The temperature of the hot wire chemical vapor deposition reaction chamber is raised to 1600°C~2000°C, the reaction chamber is evacuated, and then 200sccm~1000sccm of SiH4, 100sccm~1000sccm of PH3, and 1500sccm~3000sccm of H2 are introduced to decompose them, and the decomposed reaction gas is introduced into the chamber containing the sample to be processed. The pressure of the reaction chamber is controlled at 20Pa~150Pa, and deposition is performed for 4min~8min to form an amorphous silicon layer or a polycrystalline silicon layer containing doped elements.

[0061] After forming a polysilicon layer or an amorphous silicon layer containing doping elements, it is subjected to heat treatment and microwave treatment at the same time to obtain a doped polysilicon material with a high concentration of doping elements.

[0062] In some specific implementations, heat treatment is performed on a polysilicon layer or an amorphous silicon layer containing doping elements to activate the doping elements and increase the concentration of the doping elements. In some specific implementations, heat treatment is performed under a nitrogen or oxygen atmosphere. The N2 atmosphere can increase molecular collisions to make the thermal field more uniform. The O2 atmosphere can increase molecular collisions and react with the substrate to generate a layer of oxide on the surface. In some specific implementations, the temperature of the heat treatment is 600°C to 950°C, which can be 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, preferably 750°C to 950°C, and more preferably 800°C to 950°C. In some specific implementations, the heat treatment time is 20 min to 60 min, which can be 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, preferably 30 min to 50 min, and more preferably 35 min to 45 min.

[0063] In the present application, microwave treatment is performed while heat treating the polycrystalline silicon layer or amorphous silicon layer containing doping elements to further increase the concentration of the doping elements. The high-frequency electromagnetic field generated by microwaves can change the state of the material, making it achieve a more stable structure and performance; under the action of the microwave field, the molecules of the material will generate heat, thereby changing the structure of the material; microwaves can change the lattice and chemical structure of the material, while improving the performance of the material, it can also shorten the process time, thereby improving the efficiency of the manufacturing process. During the microwave treatment process, its power, frequency and time, especially power, are important factors that affect the activation of doping elements. Controlling it within a certain range makes it easier to activate the doping elements. In some specific implementations, the power of the microwave treatment is 50W to 1000W, which can be 50W, 100W, 200W, 500W, 700W, 800W, 900W, 1000W, preferably 100W to 800W, and more preferably 400W to 600W; the time of the microwave treatment is 5min to 60min, which can be 5min, 10min, 15min, 20min, 30min, 40min, 50min, 55min, 60min; the frequency of the microwave treatment is 300MHz to 300GHz, which can be 300MHz, 800MHz, 1GHz, 1.26GHz, 5GHz, 10GHz, 100GHz, 200GHz, 300GHz, preferably 800MHz to 100GHz, and more preferably 1GHz to 10GHz. In the heat treatment process, in an N2 or O2 atmosphere, high temperature and microwave treatment are applied simultaneously to activate more doping elements P or B, thereby greatly increasing the doping concentration of the POLY layer. Compared with the case of only high-temperature heat treatment, the doping concentration is further increased, breaking through the original doping concentration threshold.

[0064] The present application has no special restrictions on the equipment for performing the heat treatment and the microwave treatment at the same time, which can be a microwave annealing furnace. Accordingly, the present application provides a microwave annealing furnace, including:

[0065] A heating chamber is provided with a high-frequency coil for generating microwaves outside the heating chamber, a quartz chamber is provided inside the heating chamber, and a quartz boat for carrying samples is provided inside the quartz chamber.

[0066] See also Figure 3 , Figure 3 This is a schematic structural diagram of a microwave annealing furnace provided in an embodiment of the present application, wherein 11 is a high-frequency coil, 12 is a heating cavity, 13 is a quartz boat, 14 is a quartz cavity, and 10 is a sample to be processed.

[0067] The microwave annealing furnace has a heating cavity 12 for heating a quartz cavity 14 disposed therein, and a quartz boat 13 is disposed inside the quartz cavity 14 for holding the sample to be processed 10. In some specific implementations, the quartz boat 13 includes quartz boats disposed relatively parallel to each other, and a plurality of samples to be processed are placed between two quartz boats, which can improve the processing efficiency.

[0068] A high-frequency coil 11 is disposed outside the heating cavity 12 for generating microwaves to achieve microwave treatment while performing heat treatment.

[0069] The microwave annealing furnace provided in the present application can be used to perform microwave treatment on the sample while performing heat treatment, thereby increasing the doping concentration of the doping element.

[0070] In the present application, after forming a polycrystalline silicon layer or an amorphous silicon layer containing doping elements, the layer is subjected to a heat treatment and a microwave treatment at the same time. By setting the power of the microwave treatment to 50W to 1000W, the doping concentration (the amount of activated ions doped in the matrix) is greatly increased. In a typical embodiment, the heat treatment and the microwave treatment at the same time can increase the doping concentration of the original sample from 5×10 20 cm -3 Up to 5.5×10 20 cm -3 Increased to 0.8×10 21 cm -3 Up to 2×10 21 cm -3 , the improvement can reach 60%~100%, thereby improving the battery passivation performance and reducing contact resistance and transmission resistance.

[0071] The present application also provides a doped polysilicon material, comprising a silicon substrate, a tunneling oxide layer and a doped polysilicon layer stacked in sequence, wherein the doping concentration of the doped polysilicon layer is 0.8×10 21 cm -3 Up to 2×10 21 cm -3 .

[0072] See also Figure 4 , Figure 4 Schematic diagram of the stacked structure of the doped polysilicon material provided in this application, wherein 500 is a substrate, 501 is a tunneling oxide layer, and 502 is a doped polysilicon layer. The materials, parameters and preparation processes of each layer are the same as those described above, and this application will not repeat them here.

[0073] The present application also provides a method for preparing a TOPCON battery, comprising:

[0074] A textured surface and an emitter are sequentially formed on the first surface of the substrate, and a tunneling oxide layer and a polysilicon layer or an amorphous silicon layer containing doping elements are sequentially formed on the second surface, and the obtained material is subjected to a heat treatment and a microwave treatment at the same time to convert the polysilicon layer or the amorphous silicon layer containing doping elements into a doped polysilicon layer; the power of the microwave treatment is 50W to 1000W;

[0075] forming a passivation film and a first anti-reflection film on the emitter in sequence, and forming a second anti-reflection film on the surface of the doped polysilicon layer;

[0076] A first electrode and a second electrode are formed on the surfaces of the first anti-reflection film and the second anti-reflection film respectively.

[0077] The present application first forms a textured surface and an emitter on the first surface of the substrate, for example, the front surface. The present application has no special restrictions on the textured method, the emitter formation method and parameters. For example, the textured surface can be formed into a pyramid textured surface by a wet method; when the doping element is P, the emitter can be an emitter formed by B diffusion.

[0078] Then, on the second surface of the substrate, for example, the front tunneling oxide layer and the polycrystalline silicon layer or amorphous silicon layer containing the doping elements are subjected to heat treatment and microwave treatment at the same time, so as to convert the polycrystalline silicon layer or amorphous silicon layer containing the doping elements into a doped polycrystalline silicon layer. This process is the same as the process described above and will not be repeated in this application.

[0079] After forming the doped polysilicon layer, a passivation film and a first anti-reflection film are formed on the emitter. The present application has no special restrictions on the formation method and parameters of the passivation film and the first anti-reflection film. For example, the passivation film can be an AlOx passivation film, and the first anti-reflection film can be a SiNx anti-reflection film, etc. Those skilled in the art can make a selection according to actual needs.

[0080] Then, a second anti-reflection film is formed on the surface of the doped polysilicon layer. The present application has no special restrictions on the formation method and parameters of the second anti-reflection film. For example, the second anti-reflection film can be a SiNx anti-reflection film.

[0081] Finally, a first electrode and a second electrode are formed on the surfaces of the first anti-reflection film and the second anti-reflection film, respectively, to obtain a TOPCON cell. The present application has no special restrictions on the formation method and parameters of the first electrode and the second electrode. For example, the first electrode and the second electrode can be independently silver electrodes, and those skilled in the art can select them according to actual needs.

[0082] The present application also provides a TOPCON cell, comprising the doped polysilicon material described in the above technical solution. Figure 5 , Figure 5Schematic diagram of the stacked structure of the TOPCON cell provided in the present application, wherein 1 is a velvet surface, 2 is an emitter, 3 is a passivation film, 4 is a second anti-reflection film, 5 is a second electrode, 6 is a tunneling oxide layer, 7 is a doped polysilicon layer, 8 is a first anti-reflection film, 9 is a first electrode, and 10 is a substrate.

[0083] like Figure 5 As shown, the TOPCON cell includes a first electrode 9, a first anti-reflection film 8, a doped polysilicon layer 7, a tunneling oxide layer 6, a substrate 10, a textured surface 1, an emitter 2, a passivation film 3, a second anti-reflection film 4, and a second electrode 5, which are stacked in sequence. The present application has no special restrictions on the preparation method and parameters of each layer structure, and the preparation method described above can be referred to, and the present application will not repeat them here.

[0084] In the present application, after forming a polycrystalline silicon layer or an amorphous silicon layer containing doping elements, the layer is subjected to a heat treatment and a microwave treatment at the same time. By setting the power of the microwave treatment to 50W to 1000W, the doping concentration (the amount of activated ions doped in the matrix) is greatly increased. In a typical embodiment, the heat treatment and the microwave treatment at the same time can increase the doping concentration of the original sample from 5×10 20 cm -3 Up to 5.5×10 20 cm -3 Increased to 0.8×10 21 cm -3 Up to 2×10 21 cm -3 , the increase is 60%~100%.

[0085] In the present application, the P-doped material prepared by the above method is prepared into a TOPCON battery, which can improve the passivation performance of the battery and increase the open circuit voltage Uoc of the battery by 1mv to 2mv; reduce the contact resistance and lateral transmission resistance of the metal, for example, reduce the series resistance Rs of the battery by 0.1 milliohms to 0.2 milliohms (mohm); and improve the fill factor FF of the battery by 0.1% to 0.3%.

[0086] The present application is further described below in conjunction with the following embodiments. The protection scope of the present application is not limited by the following embodiments.

[0087] Example 1

[0088] An n-type silicon substrate was placed in a mixed solution of H2O2 and HNO3 for wet oxidation to obtain a tunneling oxide layer substrate with a tunneling oxide layer thickness of 1.6 nm. The mass fraction of each substance in the mixed solution was as follows: 3% H2O2+0.5% HNO3, the wet oxidation temperature was 50°C, and the wet oxidation time was 160s.

[0089] A polysilicon layer is formed on the surface of the tunnel oxide layer by low-pressure chemical vapor deposition, and the process is as follows: an n-type substrate formed with a tunnel oxide layer is placed in a furnace tube of a chemical vapor deposition device, the temperature is raised to 450°C, the gas in the tube is evacuated, 3000sccm of SiH4, 1400sccm of PH3 (8%PH3+92%H2) is introduced, and 8000sccm of H2 is deposited at a pressure of 400Pa for 15 minutes to form an amorphous silicon layer containing doped elements;

[0090] The polysilicon layer substrate containing doped elements is heat-treated at 850°C in an oxygen atmosphere, and is treated with microwaves with a power of 500W, a frequency of 1.26GHz, and a wavelength of 50mm. The microwave treatment is stopped after 15 minutes, and the heat treatment is continued for a total of 30 minutes to obtain a doped polysilicon material.

[0091] The ECV test was performed on the doped polysilicon material, and the results were as follows: Figure 6 As shown, Figure 6 The ECV (activation concentration) test result diagram of the doped crystalline silicon material provided in Example 1 of the present application is shown in FIG. Figure 6 It can be seen that the doping concentration of the doped polysilicon material prepared by the method of Example 1 can reach up to 1.1×10 21 cm -3 .

[0092] Embodiments 2 to 10

[0093] The difference from Example 1 is that the heat treatment parameters or microwave treatment parameters are different. The parameters are detailed in Table 1, which shows the treatment parameters of the embodiments and comparative examples of the present application;

[0094] The obtained doped polysilicon material was tested, and the results are shown in Table 2. Table 2 shows the doping concentration results of the doped polysilicon materials prepared in the examples and comparative examples of the present application.

[0095] Comparative Example 1

[0096] The difference from Example 1 is that only heat treatment is performed without microwave treatment. The parameters are detailed in Table 1, which shows the processing parameters of the embodiments of the present application and the comparative examples;

[0097] The obtained doped polysilicon material was tested, and the results are shown in Table 2. Table 2 shows the doping concentration results of the doped polysilicon materials prepared in the examples and comparative examples of the present application.

[0098] Comparative Example 2

[0099] The difference from Example 1 is that only microwave treatment is performed without heat treatment. The parameters are detailed in Table 1, which shows the processing parameters of the examples and comparative examples of the present application;

[0100] The obtained doped polysilicon material was tested, and the results are shown in Table 2. Table 2 shows the doping concentration results of the doped polysilicon materials prepared in the examples and comparative examples of the present application.

[0101] Comparative Examples 3~5

[0102] The difference from Example 1 is that the heat treatment parameters or microwave treatment parameters are different. The parameters are detailed in Table 1, which shows the treatment parameters of the embodiments and comparative examples of the present application;

[0103] The obtained doped polysilicon material was tested, and the results are shown in Table 2. Table 2 shows the doping concentration results of the doped polysilicon materials prepared in the examples and comparative examples of the present application.

[0104] Table 1 Processing parameters of the present embodiment and comparative example

[0105]

[0106] Application Examples 1~15

[0107] The doped polysilicon materials obtained in Examples 1 to 10 and Comparative Examples 1 to 5 were prepared into N-topcon cells (182 mm×182 mm), specifically comprising the following steps:

[0108] Step 1: Performing texturing on the front side of the n-type substrate to form a pyramid texture surface;

[0109] Step 2: Boron diffusion is performed on the pyramid velvet surface to form an emitter;

[0110] Step 3: Polish the back side to form a smooth square velvet surface on the back side;

[0111] Step 4: preparing a tunnel oxide layer and doped amorphous silicon on the back side;

[0112] Step 5: Perform high temperature annealing and microwave treatment to activate doping impurities;

[0113] Step 6: Clean the side insulation and the front BSG;

[0114] Step 7: forming a front AlOx passivation film;

[0115] Step 8: forming a front SiNx anti-reflection film;

[0116] Step 9: forming a back SINX anti-reflection film;

[0117] Step 10: Form silver electrodes on the front and back sides respectively, sinter to form ohmic contacts, and perform laser treatment to enhance the ohmic contacts.

[0118] The electrical performance parameters of the batteries provided in application examples 1 to 15 are tested using a halm machine, as shown below:

[0119] (1) Open circuit voltage of the battery:

[0120] (2) Short-circuit current:

[0121] (3) Resistance:

[0122] (4) Filling factor:

[0123] (5) Conversion efficiency

[0124] The performance test results are shown in Table 2.

[0125] Table 2

[0126]

[0127] As shown in Table 1, the P doping concentration of the doped polysilicon material prepared by the method provided by the present invention is relatively high, which can be increased to 2×10 21 cm -3 As shown in Table 2, the TOPCON battery prepared in this way has better performance in terms of open circuit voltage, resistance and fill factor. The open circuit voltage Uoc can be increased by 1~2mv, the series resistance Rs of the battery can be reduced by 0.1 milliohms~0.2 milliohms (mohm), and the fill factor FF can be increased by 0.1%~0.3%.

[0128] The above is only a preferred specific implementation manner of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can make equivalent substitutions or changes within the technical scope disclosed in the present application according to the technical solution and application concept of the present application, which should be covered by the protection scope of the present application.

Claims

1. A method for preparing a doped polysilicon material, It is characterized in that include: A tunneling oxide layer and a polysilicon layer or an amorphous silicon layer containing doping elements are sequentially formed on the surface of the substrate, and the obtained material is subjected to heat treatment and microwave treatment at the same time to obtain a doped polysilicon material; The power of the microwave treatment is 50W to 1000W.

2. The preparation method according to claim 1, It is characterized in that The time of the microwave treatment is 5 min to 60 min, and the frequency of the microwave treatment is 300 MHz to 300 GHz.

3. The preparation method according to claim 2, It is characterized in that The power of the microwave treatment is 100 W to 800 W, the frequency of the microwave treatment is 800 MHz to 100 GHz, and the time of the microwave treatment is 10 min to 50 min.

4. The preparation method according to claim 1, It is characterized in that The heat treatment is performed at a temperature of 600° C. to 1200° C. in an atmosphere of nitrogen or oxygen. The heat treatment lasts for 20 min to 60 min.

5. The preparation method according to claim 1, It is characterized in that The thickness of the tunnel oxide layer is 0.1 nm to 2.5 nm.

6. The preparation method according to claim 1, It is characterized in that The polysilicon layer or amorphous silicon layer containing doping elements is formed by the following method: forming a polysilicon layer or an amorphous silicon layer on the surface of the tunnel oxide layer; forming a diffusion source on the surface of the polycrystalline silicon layer or the amorphous silicon layer, and forming a polycrystalline silicon layer or an amorphous silicon layer containing doping elements after heat treatment; Alternatively, a polycrystalline silicon layer or an amorphous silicon layer containing doping elements is formed according to the following method: Silicon-containing gas, doping element-containing gas and carrier gas are vapor-deposited on the surface of the tunneling oxide layer to form a polysilicon layer or an amorphous silicon layer containing doping elements.

7. A doped polysilicon material, It is characterized in that The invention comprises a substrate, a tunnel oxide layer and a doped polysilicon layer stacked in sequence, wherein the doping concentration of the doped polysilicon layer is 0.8×10 21 cm -3 Up to 2×10 21 cm -3 .

8. A TOPCON battery, It is characterized in that Comprising the doped polysilicon material as claimed in claim 7.

9. A method for preparing a TOPCON battery, It is characterized in that include: A textured surface and an emitter are sequentially formed on the first surface of the substrate, and a tunneling oxide layer and a polysilicon layer or an amorphous silicon layer containing doping elements are sequentially formed on the second surface, and the obtained material is subjected to a heat treatment and a microwave treatment at the same time to convert the polysilicon layer or the amorphous silicon layer containing doping elements into a doped polysilicon layer; the power of the microwave treatment is 50W to 1000W; forming a passivation film and a first anti-reflection film on the emitter in sequence, and forming a second anti-reflection film on the surface of the doped polysilicon layer; A first electrode and a second electrode are formed on the surfaces of the first anti-reflection film and the second anti-reflection film respectively.

10. A microwave annealing furnace, It is characterized in that The heating chamber comprises a heating chamber, the outside of which is provided with a high-frequency coil for generating microwaves, the inside of which is provided with a quartz chamber, and the inside of which is provided with a quartz boat for carrying samples.

Citation Information

Cited By

  • Passivating film layer, preparation method thereof and solar cell

    CN120640835A